LITERATURE REVIEW: FACTORS AFFECTING FINAL YEAR STUDENTS' ANXIETY IN PREPARING A THESIS IN INDONESIA - Izza, Ania Al; Lailiyah, Syifaul (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2024)
Background: Thesis or final project is often used as a graduation requirement by most campuses in Indonesia. Writing a thesis is often considered terrifying because students often experience difficulties. This triggers anxiety and even depression for final year students for fear of not being able to complete their thesis writing. Purpose: To find out the factors that influence the anxiety of final year students in preparing a thesis. Methods: Literature study research using national articles with published years 2018-2023. Articles were searched using the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) method. Inclusion criteria included publication of articles reviewed no more than the last ten years, titles still related to keywords, quantitative or qualitative research, and full text. Exclusion criteria were articles published more than ten years, titles not related to keywords, and inaccessible. Database using google scholar. Results: Factors that influence the anxiety of final year students in preparing a thesis come from internal and external factors. Conclusion: Internal factors, such as lack of self-confidence, self-efficacy, self-discipline, fighting power, self-control, and high perfectionism. External factors, such as supervising lecturers, lack of parental and family support, and peer support. Abstrak Latar belakang: Skripsi atau tugas akhir seringkali dijadikan syarat kelulusan oleh sebagian besar kampus di Indonesia. Penulisan skripsi seringkali dianggap menakutkan karena sering kali mahasiswa mengalami kesulitan. Hal tersebut memicu munculnya kecemasan bahkan depresi bagi mahasiswa tingkat akhir karena takut tidak bisa menyelesaikan penulisan skripsinya. Tujuan: Mengetahui faktor-faktor yang mempengaruhi kecemasan mahasiswa tingkat akhir dalam menyusun skripsi. Metode: Penelitian studi literatur menggunakan artikel nasional dengan tahun terbit 2018-2023. Penelusuran artikel menggunakan metode Preferred Reporting Items for Systematic Review & Meta-Analyses (PRISMA). Kriteria inklusi berupa terbitan artikel yang di-review tidak lebih dari sepuluh tahun terakhir, judul masih berhubungan dengan kata kunci, penelitian kuantitatif atau kualitatif, dan full text. Kriteria eksklusi berupa terbitan artikel lebih dari sepuluh tahun, judul tidak berhubungan dengan kata kunci, dan tidak dapat diakses. Data base menggunakan google scholar. Hasil: Faktor-faktor yang mempengaruhi kecemasan mahasiswa tingkat akhir dalam menyusun skripsi bersumber dari faktor internal dan eksternal. Kesimpulan: Faktor internal, seperti kurangnya kepercayaan diri, efikasi diri, kedisiplinan diri, daya juang, kontrol diri, dan tingginya sikap perfeksionisme. Faktor eksternal, seperti faktor dosen pembimbing, kurangnya dukungan orang tua dan keluarga, serta dukungan teman sebaya.